2017
DOI: 10.1016/j.ijscr.2017.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Transverse testicular ectopia with inguinal hernia – A rare case report

Abstract: HighlightsIt is a rare anomaly of abnormal testicular migration.It was seen in a 24 year old with associated left inguinal hernia.He underwent left sided meshplasty and orchidectomy.It is usually discovered on surgical exploration.It’s important due to risk of malignant transformation of the ectopic testis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Ultrasound showed no testis echoes on one side of the scrotum and groin, while two testes echoes were observed in the contralateral scrotum, groin, or abdominal cavity. Previous studies have reported that TTE was more common in the contralateral scrotum, and our results are consistent with previous case reports ( 4 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Ultrasound showed no testis echoes on one side of the scrotum and groin, while two testes echoes were observed in the contralateral scrotum, groin, or abdominal cavity. Previous studies have reported that TTE was more common in the contralateral scrotum, and our results are consistent with previous case reports ( 4 ).…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have suggested that the occurrence of TTE is related to persistent Müllerian duct syndrome (PMDS) (4)(5)(6). Children with TTE often present with a scrotal emptiness or a groin mass.…”
Section: Introductionmentioning
confidence: 99%
“…Transverse Testicular Ectopia (TTE) is a congenital abnormality that is characterized by descending the testis through the same inguinal canal toward the hemiscrotum [ 1 ] [ 2 ]. Furthermore, it usually occurs in patients with undescended testes or operated for inguinal hernia [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transverse Testicular Ectopia is a rare congenital anomaly characterized by the descent of both testes through the same inguinal canal or hemiscrotum [ 1 , 2 ]. Transverse Testicular Ectopia (TTE) is an even rarer occurrence, with an estimated incidence of 1 in every 4 million children [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation